Additive manufacture of an aluminium alloy: processing, microstructure, and mechanical properties - Aboulkhair, Nesma T. (2016)
Additive manufacturing of aluminium alloys using selective laser melting (SLM) is of research interest nowadays because of its potential benefits in industry sectors such as aerospace and automotive. However, in order to demonstrate the credibility of aluminium SLM for industrial needs, a comprehensive understanding of the interrelation between the process parameters, produced microstructure, and mechanical behaviour is still needed. This thesis aims at contributing to developing this comprehensive understanding through studying the various aspects of the process, with investigation of the powder raw material to the near fully dense samples, focussing on the alloy AlSi10Mg.